The Effect of Colistin Resistance-Associated Mutations on the Fitness of Acinetobacter baumannii - Mu, Xinli; Wang, Nanfei; Li, Xi; Shi, Keren; Zhou, Zhihui; Yu, Yunsong; Hua, Xiaoting (Frontiers in Microbiology, 2016)
Acinetobacter baumannii had emerged as an important nosocomial and opportunistic pathogen worldwide. To determine the evolutionary pathway of colistin resistance in A. baumannii and its influence on bacterial fitness, five independent colonies of A. baumannii ATCC 17978 were exposed to colistin in agar (4/5) and liquid media (1/5) with increasing and constant concentrations. Stable resistance isolates were sent for whole genome sequencing. All strains were colistin resistant after exposure to colistin. In addition to the previously reported lpxCAD and pmrAB mutations, we detected four novel putative colistin resistance genes: A1S_1983, hepA, A1S_3026, and rsfS. Lipopolysaccharide (LPS) loss mutants exhibited higher fitness costs than the pmrB mutant in nutrient-rich medium. The colistin-resistant mutants showed higher inhibition ratio in the serum growth experiment than the wild type strain in 100% serum. The MIC results showed that the LPS-deficient but not the pmrB mutant altered the antibiotic resistance profile. The compensatory mutations partially or completely recovered the LPS-deficient’s fitness, suggesting that compensatory mutations played an important role in the emergence and spread of colistin resistant A. baumannii.